Effects of organic additives on the immersion gold depositing from a sulfite–thiosulfate solution in an electroless nickel immersion gold process. Issue 12 (25th January 2016) - Wang, Yao; Liu, Haiping; Bi, Sifu; He, Mengxue; Wang, Chunyu; Cao, Lixin
Abstract : An immersion gold-plating process on electroless Ni–P alloy substrate was investigated. Abstract : An immersion gold-plating process on electroless Ni–P alloy substrate was investigated. The immersion Au coating was deposited from a thiosulfate–sulfite mixed ligand bath based on Ni–P alloy substrate. The effects of three organic additives, such as polyethylenimine (PEI), hexamethylene tetramine (HET) and benzotriazole (BTA) on the depositing process and the performance of Au coating were investigated. The study was performed by measuring the open circuit potential–time curves in situ and Tafel tests in combination with X-ray fluorescence spectrometry (XRF), scanning electron microscope (SEM), Raman spectroscopy and X-ray diffraction (XRD) analysis techniques. The results show that PEI, HET and BTA could adsorb and desorb on the surface of Au coating and they had the similar influences on the open circuit potential. With these organic compounds adding, the plateau potential shifts to the positive direction, and the time for the potential to reach the plateau value decreases with increasing additive concentration. The XRF, XRD and SEM studies indicated that these three additives decreased the initial deposition rate, decreased the size of Au particles, and thus changed the morphology of Au deposits. Tafel studies demonstrated that the corrosion resistance of Au coating could be improved by adding PEI, HET or BTA to immersion gold bath. A cause for understanding these additives was indicated based on the above experiments.